Digital data collection in paleoanthropology. Issue 6 (November 2015) - Reed, Denné; Barr, W. Andrew; Mcpherron, Shannon P.; Bobe, René; Geraads, Denis; Wynn, Jonathan G.; Alemseged, Zeresenay
Abstract : Understanding patterns of human evolution across space and time requires synthesizing data collected by independent research teams, and this effort is part of a larger trend to develop cyber infrastructure and e‐science initiatives.1 At present, paleoanthropology cannot easily answer basic questions about the total number of fossils and artifacts that have been discovered, or exactly how those items were collected. In this paper, we examine the methodological challenges to data integration, with the hope that mitigating the technical obstacles will further promote data sharing. At a minimum, data integration efforts must document what data exist and how the data were collected (discovery), after which we can begin standardizing data collection practices with the aim of achieving combined analyses (synthesis). This paper outlines a digital data collection system for paleoanthropology. We review the relevant data management principles for a general audience and supplement this with technical details drawn from over 15 years of paleontological and archeological field experience in Africa and Europe. The system outlined here emphasizes free open‐source software (FOSS) solutions that work on multiple computer platforms; it builds on recent advances in open‐source geospatial software and mobile computing.